Предмет: Алгебра,
автор: nastasya0203
помогите пожалуйста, решени как можно подробнее (8)
Приложения:
Ответы
Автор ответа:
0
Получится вот так :)
Приложения:
Автор ответа:
0
пожалуйста)
Автор ответа:
0
=Х(Х²+3)/(Х+√3)=Х(Х+√3)
=(2m/(2m+n)-4m²/(2m+n)²):(2m/(2m-n)(2m+n)-1/(2m-n))=
=(4m²+2mn-4m²)/(2m+n)²×((2m-n)(2m+n))/(-n)=-(2mn(2m-n))/(2m+m)
=(2m/(2m+n)-4m²/(2m+n)²):(2m/(2m-n)(2m+n)-1/(2m-n))=
=(4m²+2mn-4m²)/(2m+n)²×((2m-n)(2m+n))/(-n)=-(2mn(2m-n))/(2m+m)
Приложения:
Похожие вопросы
Предмет: Химия,
автор: Doc120
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Математика,
автор: pashkevichakbota3
Предмет: Химия,
автор: jenea78541
Предмет: Химия,
автор: Милка3746